Rapid broth macrodilution method for determination of MICs for Mycobacterium avium isolates. - Siddiqi, S H (1993)
A multicenter study was done to investigate the accuracy and reproducibility of a method for determining the MICs of antimicrobial agents against the Mycobacterium avium complex in 7H12 broth with the BACTEC system. In phase I, with eight drugs and 10 strains, intralaboratory reproducibility was 95.7 to 100%, allowing a 1-dilution difference upon repeat testing. The results of phase II testing with 41 additional strains were consistent with those obtained in phase I, with good interlaboratory reproducibility. The radiometric method was validated by sampling and plating of the same broth cultures and determining, by the number of CFU per milliliter, the lowest drug concentration that inhibited more than 99% of the initial bacterial population. Three test concentrations of each drug and the tentative interpretation of results are proposed. Radiometric MIC determination has the potential to become the method of choice for clinical microbiology laboratories and evaluation of new agents for the treatment of M. avium infections, both pulmonary and disseminated.